2005
DOI: 10.1002/bjs.4976
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of daclizumab induction and delayed introduction of tacrolimus for recipients of non-heart-beating kidney transplants

Abstract: Induction with DZB and delayed introduction of tacrolimus reduced the incidence of DGF in recipients of machine-perfused NHBD kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…58 A prospective randomized trial of 51 recipients of NHB donor kidneys performed in Newcastle upon Tyne and Leicester in the UK showed that induction therapy with the monoclonal antiinterleukin-2-receptor antibody daclizumab can be safely substituted for tacrolimus in the early postoperative period. 59 The duration of DGF did not differ between groups, except for in a subgroup of machine-perfused kidneys in which induction treatment with daclizumab reduced the incidence of DGF. Rates of acute rejection and duration of hospitalization were similar in the two main study groups.…”
Section: Discussionmentioning
confidence: 83%
“…58 A prospective randomized trial of 51 recipients of NHB donor kidneys performed in Newcastle upon Tyne and Leicester in the UK showed that induction therapy with the monoclonal antiinterleukin-2-receptor antibody daclizumab can be safely substituted for tacrolimus in the early postoperative period. 59 The duration of DGF did not differ between groups, except for in a subgroup of machine-perfused kidneys in which induction treatment with daclizumab reduced the incidence of DGF. Rates of acute rejection and duration of hospitalization were similar in the two main study groups.…”
Section: Discussionmentioning
confidence: 83%
“…randomized 51 recipients of DCD kidney transplants to induction with daclizumab and daily MMF and compared them with no induction but a standard tacrolimus‐based triple therapy without induction. Although they found a decreased incidence of DGF in daclizumab‐induced recipients with delayed introduction of calcineurin inhibitors, outcome beyond 3 months was not presented [11]. Rivera et al.…”
Section: Discussionmentioning
confidence: 99%
“…DCD transplants have been related to a higher incidence of DGF, PNF, and, in some reports, to a higher incidence of AR . In most centers, these results were obtained with CNI‐based immunosuppressive regimens, but with minimization of CNI exposure .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have proposed minimization of CNI therapy in DCD transplants to avoid DGF, with satisfactory survival and functioning grafts . Other authors have also proposed a CNI‐free treatment and an mTOR‐I‐based therapy in DCD transplants to avoid DGF, with good graft and patient survival .…”
Section: Introductionmentioning
confidence: 99%